Modeling serological testing to inform relaxation of social distancing for COVID-19 control - Alicia N. M. Kraay (Nature Portfolio, 2021)
Serological testing remains a passive component of the current public health response to the COVID-19 pandemic. Using a mathematical model, the authors examine how testing for antibodies could have enabled policies in which seropositive individuals increased their relative levels of social interaction while offsetting transmission risks